COORDINATOR TEACHERS UNDER THE TEACHER'S VIEW - Oliveira, Luciane Aparecida de; Chaluh, Laura Noemi [UNESP] (Univ Metodista Piracicaba-unimep, 2019)
In this work, we analyze a snippet of a research that aimed to understand the formation of teachers and pedagogical coordinators, considering their responsibilities (administrative and pedagogical) and the relationships they establish with the school community (management, teachers, clerks, students and parents), together with the Municipal Secretary of Education (SME) of a city in the interior of the State of Sao Paulo. The research focused in the challenges that those subjects faced and were present within a Study Group, under the responsibility of the pedagogical coordinator associated to the SME. The theoretical-methodological perspective assumed was the narrative research. In this work, we share a survey realized by the coordinating teachers in their respective schools and which results report the teachers' perceptions regarding the assignments of the coordinating teachers. We expose the lessons learned by the pedagogical coordinator, in charge of the Study Group, which show the concepts of the formation of coordinating teachers and their implications when thinking about them as articulators of formation in the school context. To compose the work, we bring the records made by the teachers and the pedagogical coordinator. This work contributes to rethink the formative processes in the context of educational networks.
Keywords: Coordinating teacher; Continuing education; Educational network